Acesso din??mico ao espectro habilitado por base de dados e internet das coisas - Pereira, Elivander Judas Tadeu (2020)
With the growth in the number of wireless devices, spectrum scarcity has become an issue. Faced with this problem, many regulatory agencies around the world studied new ways to increase the spectral efficiency of radio frequency bands. Among the alternatives, the dynamic spectrum access is made possible by a database and also the use of opportunistic access techniques through spectrum sensing. However, it is known that these individual models may not lead to the maximum possible efficiency, or even, they may not ensure proper safety for primary users. Aiming to solve these problems, this work brings a study with the idealization of a spectrum sensing infrastructure based on IoT networks, which associated with a database, provides all the necessary tools for spectrum management, enabling opportunistic secondary networks, ensuring users security, greater accuracy and reliability on spectrum usage, as well as a spectrum market among users based on a smart contract. In this conception, the most conservative approach using a database works in conjunction with the proposed infrastructure for the sensing network, intending to keep up to date with the most accurate information on spectrum occupation in real-time.